Upaya Peningkatan Konsumsi Tablet Fe terhadap Kejadian Anemia pada Ibu Hamil - Probowati, Rovica; Anggorowati, Anggorowati; Agushybana, Farid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze complications in pregnancy and childbirth caused by iron deficiency in pregnant women. The research method uses a literature review with a library approach using existing databases Pubmed, Google Scholar, and Portal Garuda. The research results show that the incidence of anemia in pregnant women in Indonesia has not reached the target due to a lack of knowledge and attitudes of pregnant women about the importance of blood supplement tablets during pregnancy. In conclusion, efforts to consume fe tablets are influenced by factors that must be improved. Regular visits by health workers and assistance from the family are the most influential factors for improving health education for pregnant women. Keywords: Pregnant Women, Anemia Prevention, Fe Tablets